Organochlorine residues in Spanish common pipistrelle bats (Pipistrellus pipistrellus) - Guilln, A.; Ibez, C.; Prez, J.L.; Hernndez, L.M.; Gonzlez, M.J.; Fernndez, M.A.; Fernndez, R. (Zenodo, 1994)
(Uploaded by Plazi for the Bat Literature Project) No abstract provided.